2022
DOI: 10.1016/j.amepre.2021.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Parental Vaccine Hesitancy and Association With Childhood Diphtheria, Tetanus Toxoid, and Acellular Pertussis; Measles, Mumps, and Rubella; Rotavirus; and Combined 7-Series Vaccination

Abstract: Introduction: Parental vaccine hesitancy can be a barrier to routine childhood immunization and contribute to greater risk for vaccine-preventable diseases. This study examines the impact of parental vaccine hesitancy on childhood vaccination rates.Methods: This study assessed the association of parental vaccine hesitancy on child vaccination coverage with ≥4 doses of diphtheria, tetanus toxoid, and acellular pertussis vaccine; ≥1 dose of measles, mumps, and rubella vaccine; up-to-date rotavirus vaccine; and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Fast-waning immunity and genetic adaptation also contribute to the increasing pertussis incidence. In addition, parental vaccine hesitancy can contribute to a greater risk for vaccine-preventable diseases including pertussis [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fast-waning immunity and genetic adaptation also contribute to the increasing pertussis incidence. In addition, parental vaccine hesitancy can contribute to a greater risk for vaccine-preventable diseases including pertussis [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with prior research showing lower vaccination rates among racial and ethnic minority groups and younger individuals. 5 Further research is needed to understand the reasons for this gap and to identify opportunities to proactively connect such individuals with credible resources for decision‐making. In the context of COVID‐19 vaccines specifically, vaccination rates among racial and ethnic minority populations were lower compared with Whites in the general population at the time of our study.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 Non‐adherence of parents to the recommended childhood vaccination schedule for reasons other than vaccine availability is termed parental vaccine hesitancy. 3 In an analysis of data from the 2018 and 2019 US National Immunization Survey, Nguyen et al 5 identified hesitancy towards childhood vaccines in 23.6% of surveyed parents. Other data suggest that COVID‐19 vaccination rates among children younger than 12 years were only 30% as of July 15, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the goal of any vaccination campaign is to achieve vaccine-induced herd immunity as quickly as possible in order to prevent further transmission of disease [ 1 ]. However, data suggest a level of hesitancy among individuals when determining whether or not to receive a COVID-19 vaccine—a hesitancy that extends from childhood [ 2 ] and adult vaccines [ 3 ] to the novel H1N1 influenza pandemic [ 4 ] and COVID-19 pandemic vaccines [ 5 ]. Research indicates that COVID-19 vaccine hesitancy occurs across a heterogeneous group of individuals based on sex, race, ethnicity, and country of origin [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%